1986
DOI: 10.1038/bjc.1986.132
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterisation of six human colorectal adenocarcinoma cell lines

Abstract: Summary The establishment and characterisation (morphology, ultrastructure, tumourigenicity) of six cell lines from primary human colorectal adenocarcinomas is described. These lines were established from surgical specimens, from 49 unselected patients, without the use of 'feeder' cells, 'conditioned' medium or passage of cells in nude mice. The six cell lines exhibit considerable variation in morphology, CEA secretion and tumourigenicity in nude mice. At least two of the lines retain some of the differentiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
2

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 6 publications
2
15
1
2
Order By: Relevance
“…These results also point to an heterogeneity at the level of a unique tumor site because surgical tumor samples F320 and F329 gave rise to two pairs of distinct but closely related cell lines. Variability in genotype and phenotype of low-passage colon cancer cell lines, reflecting the diversity of the parental colon cancer cells in vivo, has already been reported (21)(22)(23)28). However, the diversity described in the latter studies was generally related to specimens originating from colon carcinomas collected from several patients and/or from specimens collected at different locations, whereas the present study further highlights biological intratumoral heterogeneity observed at a unique site.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…These results also point to an heterogeneity at the level of a unique tumor site because surgical tumor samples F320 and F329 gave rise to two pairs of distinct but closely related cell lines. Variability in genotype and phenotype of low-passage colon cancer cell lines, reflecting the diversity of the parental colon cancer cells in vivo, has already been reported (21)(22)(23)28). However, the diversity described in the latter studies was generally related to specimens originating from colon carcinomas collected from several patients and/or from specimens collected at different locations, whereas the present study further highlights biological intratumoral heterogeneity observed at a unique site.…”
Section: Discussioncontrasting
confidence: 54%
“…The rate of xenograft and/or subsequent cell line success reported here seems to be as high as those reported by other investigators. Likewise, numerous studies have reported the difficulty to initiate cancer cell lines from fresh surgically removed colon tumors (20)(21)(22)(23), and our 9.7% success rate compares favorably with other attempts to establish cell lines from a large number of colorectal adenocarcinomas (22,24). However, any study has reported neither both xenografting and direct in vitro cell line establishment from the same surgical specimens nor characterization of cell lines obtained by the two processes.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Most of the colorectal cell lines have been documented (8). Others reported elsewhere include HCT-116 (9), COLO 320DM (10), SW620 and SW480 (11), VACO4S and VACOlOMS (12), and HRA19 (13 electrophoresis, the gels were dried and bands were located by autoradiography. DNA Sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Fibroblasts were, if necessary, removed selectively by differential trypsinization between passages 1 and 3 (Kirkland and Bailey 1986). At confluence, the medium was aspirated and the cells were incubated with 1 ml of 0.02 % EDTA for 5 min or longer at 37°C to remove fibroblast from the heterogeneous culture of primary cells.…”
Section: Selective Removal Of Fibroblastsmentioning
confidence: 99%